1977
DOI: 10.1111/j.1432-1033.1977.tb11730.x
|View full text |Cite
|
Sign up to set email alerts
|

The Size and Shape of Human and Bovine Antithrombin III

Abstract: Human and bovine antithrombin, purified by affinity chromatography on heparin‐agarose, have been characterized with regard to chemical composition, size, shape and conformation. Both preparations were found to contain several active components of identical or similar size but different electrical charge. Amino acid and carbohydrate analyses revealed striking similarities between human and bovine antithrombin, while immunological analyses failed to demonstrate any cross‐reactivity. The molecular weights were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0
1

Year Published

1981
1981
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(144 citation statements)
references
References 45 publications
(28 reference statements)
4
139
0
1
Order By: Relevance
“…Protein concentrations were measured spectrophotometrically with the use of specific absorption coefficients (A~.&"") of 6.7 for both intact and modified bovine antithrombin [22], 17.5 for bovine thrombin [4] and 9.4 for bovine factor X, [23]. Values of 11.0 and 7.9 were assumed for the antithrombin-thrombin and the antithrombin-factor X, complexes, respectively ; these values were calculated from the weight fractions and the absorption coefficients of the two proteins comprising each complex.…”
Section: Materials a N D Methodsmentioning
confidence: 99%
“…Protein concentrations were measured spectrophotometrically with the use of specific absorption coefficients (A~.&"") of 6.7 for both intact and modified bovine antithrombin [22], 17.5 for bovine thrombin [4] and 9.4 for bovine factor X, [23]. Values of 11.0 and 7.9 were assumed for the antithrombin-thrombin and the antithrombin-factor X, complexes, respectively ; these values were calculated from the weight fractions and the absorption coefficients of the two proteins comprising each complex.…”
Section: Materials a N D Methodsmentioning
confidence: 99%
“…Concentrations of both plasma and recombinant antithrombin were obtained by absorption measurements at 280 nm with the use of a specific absorption coefficient of 0.65 litres * g-1 cm-' and an Mr of 58000 (Nordenman et al, 1977), unless otherwise indicated.…”
Section: Vol 286 793mentioning
confidence: 99%
“…Immunodiffusion was done in a 1 % agarose gel in 0.02 Msodium phosphate/0.1 M-NaCl, pH 7.4 (Nordenman et al, 1977) with a commercial antiserum against plasma antithrombin (Dakopatts, Glostrup, Denmark).…”
Section: Protein Analysesmentioning
confidence: 99%
“…A molecular weight for antithrombin of 56000 (Nordenman et al, 1977) was used in all calculations. Heparin from pig intestinal mucosa (stage 14; Inolex Pharmaceutical Division, Park Forest South, IL, U.S.A.) was purified as described by Lindahl et al (1965).…”
Section: Methodsmentioning
confidence: 99%
“…Protein concentrations were measured spectrophotometrically, by using a previously measured specific absorption coefficient (A,lcm) of 6.7 for bovine antithrombin (Nordenman et al, 1977).…”
Section: Methodsmentioning
confidence: 99%